Phage engineering and phage‐assisted CRISPR‐Cas delivery to combat multidrug‐resistant pathogens. Issue 2 (6th August 2022) - Khambhati, Khushal; Bhattacharjee, Gargi; Gohil, Nisarg; Dhanoa, Gurneet K.; Sagona, Antonia P.; Mani, Indra; Bui, Nhat Le; Chu, Dinh‐Toi; Karapurkar, Janardhan Keshav; Jang, Su Hwa; Chung, Hee Yong; Maurya, Rupesh; et al.
Abstract: Antibiotic resistance ranks among the top threats to humanity. Due to the frequent use of antibiotics, society is facing a high prevalence of multidrug resistant pathogens, which have managed to evolve mechanisms that help them evade the last line of therapeutics. An alternative to antibiotics could involve the use of bacteriophages (phages), which are the natural predators of bacterial cells. In earlier times, phages were implemented as therapeutic agents for a century but were mainly replaced with antibiotics, and considering the menace of antimicrobial resistance, it might again become of interest due to the increasing threat of antibiotic resistance among pathogens. The current understanding of phage biology and clustered regularly interspaced short palindromic repeats (CRISPR) assisted phage genome engineering techniques have facilitated to generate phage variants with unique therapeutic values. In this review, we briefly explain strategies to engineer bacteriophages. Next, we highlight the literature supporting CRISPR‐Cas9‐assisted phage engineering for effective and more specific targeting of bacterial pathogens. Lastly, we discuss techniques that either help to increase the fitness, specificity, or lytic ability of bacteriophages to control an infection.